THE MAIN TENDENCIES OF GIRLS’ NATURAL AND MATHEMATICAL EDUCATION IN UKRAINIAN EDUCATIONAL ESTABLISHMENTS OF THE XIX – THE BEGINNING OF THE XX CENTURY - Kokhanovska, Olena (Mountain School of Ukrainian Carpaty, 2019)
The article presents the results of historical and pedagogical research of the theory and practice of the development of girls’ natural and mathematical education in the territory of Ukraine in the XIX – the beginning of the XX century. та виокремлено її тенденції. The tendencies of girls’ natural and mathematical education in Ukrainian educational establishments have been highlighted during relevant time frame. The purpose of the study is to substantiate main tendencies of the genesis of girls’ natural and mathematical education in educational establishments of Ukraine of the XIX – the beginning of the XX century. The research tools for the study scientific and bibliographic, historical and logical, chronological-systemic, problem-search and historical-genetic methods. Based on methodological tool the leading tendencies of the development of women’s natural and mathematical education have been revealed, which are represented in the separate periods: first part of XIX century characterized by legislative regulation of the education system; changing the vector of society’s attitude to women’s education; opening of the first state secondary educational institutions for girls; second part of XIX century involved the creation of a centralized system of women’s education and a legislative base of functioning of women’s educational establishments; increasing public awareness of girls’ education, creating associations and unions that had contributed to women’s natural and mathematical education, including higher education; moving away from classicism and approaching the content of girls’ natural and mathematical education to similar education for men; improving the content, forms and methods of girls’ teaching in natural and mathematical disciplines; the beginning of the XX century was marked by the government’s efforts to implement a general elementary school; unification of girls’ natural and mathematical education; restoring women’s access to higher education, including natural and mathematical; development of new concepts, further improvement and emergence of new forms, methods and teaching tools of natural and mathematical disciplines.